THE EFFECT OF TABURIA FORTIFICATION AND NUTRITION EDUCATION OF MOTHERS TO ON NUTRITIONAL STATUS OF 12-24 MONTHS OLD CHILDREN IN INDONESIA : RANDOMIZED CONTROLLED TRIAL STUDY - Yulia Wahyuni; Maria Mexitalia; M. Zen Rahfiludin (Journal of Nutrition College, 2023)
ABSTRACTBackground: Mother's nutritional knowledge and parents' feeding practices will influence children's eating behavior which have an impact on the child's growth.Objective: The purpose of this study was to determine the effects of Taburia fortification and nutrition education of mothers on the nutritional status of children in Waipare Public health center in East Nusa Tenggara.Materials and Methods: This study was a randomized controlled trial. A total of 180 mothers and their children aged 12-24 months who had malnourished (z-score -3 to -2). The group divided into teams were the intervention group (IG) (n=90) and the control group (CG) (n=90). The IG give intervention for three months. The mothers were given nutrition education, while their children were given taburia. The CG, mothers were given nutrition education. Data feeding rules obtained using a self-administered feeding practice-Questionnaire (FPQ). Dietary intake assessment of macronutrient and micronutrient three-day food records, nutritional status, and percentage of child's sick day was conducted before and after the intervention.Results: The result of the study showed that there was no significant difference in the mean increase (P> 0.01) between knowledge scores in IG and CG, post-intervention. Lower percentage of sickness among children in IG than CG. The average nutrient intake, WAZ (0.97±0.52), WLZ (1.02±0.42) of IG increased and was higher than CG after the intervention. The LAZ of IG increased (0.34±0.66 SD) while on the CG declined (0.27±0,31 SD).Conclusion: Thus, The Taburia fortification intervention was useful in improving WAZ, LAZ, WLZ in children who experienced malnutrition, but the intervention nutrition education of mothers can increase WAZ and WLZ.